Pengaruh Metode Pemasakan Terhadap Komposisi Kimia dan Asam Amino Ikan Seluang (Rasbora argyrotaenia) - Pramita Utami; Susi Lestari; Shanti Dwita Lestari (Universitas Sriwijaya, 2016)
The purpose this study was to determine the effect of different cooking methods (boiling, steaming, and deep frying) on chemical and amino acids composition of silver rasbora fish (Rasbora argyrotaenia). This method used completely randomized design (CRD) with three replications. Fresh silver rasbora served as control. During cooking, temperature was measured using thermocouple every minutes until done. The result showed that different cooking methods contributed to changes in chemical dan amino acid composition of silver rasbora fish. Steaming was the best method to maintain the high protein level of fish composed to boiling and deep frying. Results of analysis showed that the lowest water content (7.85%) was fand in deep fried fish while the lowest fat level was found in steamed fish with the value of 2.05%. The highest protein level was found in steamed fish is (12.223 mg/mL). Glutamic acid, leucine, proline and lysine were in high proportion of amino acid content in silver rasbora fish.